Impact of Social Media on Public Perception of Civil Engineering Projects - Sultan Machmud Hasan Masikki; Gamal Abdel Nasser; Muhammad Nur Afiat; Syamsu Rijal; Anita Lestari (Politeknik Ganesha Medan, 2023)
Along with the development of technology and the internet, the use of social media has been rampant in various walks of life. Social media such as Facebook, Twitter, Instagram, and others have become important platforms for sharing information, including news about civil engineering projects. The increasing number of social media users has had a significant impact on the way people understand and respond to these projects. The purpose of this study is to examine the impact of social media on public perception of civil engineering projects. The method used is a qualitative literature review that focuses on an in-depth understanding of the topic in the time span from 2004 to 2023. The main objective of this method is to identify, analyse, and synthesise relevant scientific literature that has been published in various journals, conference papers, and other academic sources accessible through Google Scholar. The study results show that the impact of social media on public perception of civil engineering projects is a significant phenomenon in today's digital age. Social media influences the way the public perceives, participates and responds to these projects.